Metabolism-perfusion imaging to predict disease activity in cardiac sarcoidosis - Isiguzo, M.; Brunken, R.; Tchou, et al., P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
FDG-PET is a sensitive but not specific test for myocardial sarcoidosis and its ability to define prognosis remains unclear. Combination with perfusion scanning may improve accuracy by differentiating scar from inflammation. We conducted this retrospective chart review to ascertain the utility of a rubidium -FDG PET scan for assessment of disease activity in patients with cardiac sarcoidosis. The presence of any perfusionmetabolism mismatch or a mismatch of > 6% of the myocardium on the scan were compared with the clinical course. Among 18 subjects, mismatched segments were present in 11 scans, whereas 7 demonstrated mismatch > 6%. There was a suggestion of association between PET scan and active disease using the threshold of any mismatch (p=0.09), with sensitivity of 80% and specificity of 62.5%.The threshold of >6% mismatch improved the specificity to 100% with 70% sensitivity, and the association between PET findings and clinically active disease was highly significant (p=0.0002). Eight patients had follow-up Rb-FDG PET scans, all of which were concordant with the clinical course. The positive predictive value of Rb-FDG PET scan showing >6% mismatch for detecting clinically active cardiac sarcoidosis was 100%. However, the finding of any mismatch still portends a high chance of clinical activity. Further studies to define the utility of Rb-FDG PET scan for management of cardiac sarcoidosis are warranted.